Kelengkapan Pengisian Formulir Laporan Operasi Kasus Bedah Obgyn Sebagai Alat Bukti Hukum - Listia Nur Febrianti; Ida Sugiarti (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2019)
According to the Ministry of Health Decree No. 129 of 2008 concerning Minimum Standards Services in Hospitals, filling medical record include surgery report forms must be 100% that can be used as legal evidence. Preliminary study addressing 10 surgery report form of obgyn surgery cases in December 2017 wasn’t filled complete. Knowing how the implementation filling of the surgery report form of obgyn surgery cases as a legal evidence in RSUD Ciamis  District Ciamis in quarter IV 2017. Methods: Descriptive with mixed method approach, a total sample is 82 surgery report forms, and the research informant is a obgyn surgeon, coordinator of administration and medical record service, and surgical nurse. The average percentage of completeness surgery report forms of the general surgery cases in the IV quarter of 2017 was 63,78%. Inhibitory factors are limited time, patient quantity, delay in medical record control, too much items filled of form. Average percentage of surgery report form filling still below the Minimum Standards Services. Hospital should improve the causal factors that inhibit the incompleteness of surgery report form.